Angka Kejadian Ileus Obstruktif Pada Pemeriksaan BNO 3 Posisi Di RSUD Abdul Moeloek - Alfi Wahyudi; Andi Siswandi; Ratna Purwaningrum; Bella Cynthia Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Obstructive Ileus is a state where the contents of the lumen of the gastrointestinal tract cannot be transmitted to the distal due to mechanical obstruction or barriers. Causes of obstruction of ileus are related to the affected age group and obstruction location. Objective: To know the incidence of obstructive ileus on the examination of BNO 3 position in the radiology. Method: The research is a descriptive study with a cross-sectional approach. The samples in this study are all records of the medical record of obstruction ileus patients that were diagnosed through examination of the BNO 3 position. The sampling technique used a total sampling technique of 30 respondents. Data analysis using univariate analysis. Results: unknown age frequency distribution of ileus obstructive patients diagnosed through the examination of BNO 3 most vulnerable positions aged > 65 years as much as 30.0%. The most genders in male female respondents as much as 63.7% and the location of most obstructive ileus in 73.3%. Conclusion: The incidence of ileus obstrusion on most BNO examination at the age of > 65 years with male gender and the location of high-level obstruction ileus